Long-term physical training increases liver IGF-I in diabetic rats - Leme, J. A. C. A. [UNESP]; Silveira, R. F. [UNESP]; Gomes, R. J. [UNESP]; Moura, R. F. [UNESP]; Sibuya, C. A. [UNESP]; Mello, M. A. R. [UNESP]; Luciano, E. [UNESP] (Churchill Livingstone, 2009)
Diabetes reduces the serum levels of insulin-like growth factor-I (IGF-I) and physical training may prevent this reduction. Almost all circulating IGF-I is produced and secreted by the liver. To examine the influence of moderate physical training on liver IGF-I levels in diabetes, male Wistar rats were given a single dose of alloxan (30 mg/kg b.w.) to induce diabetes and then randomly allocated to sedentary or trained groups. The training protocol consisted of a 1h swimming session/day, five days/week for eight weeks with a load corresponding to 5% of the body weight. These two groups were compared with sedentary or trained non-diabetic rats (controls). A subcutaneous insulin tolerance test (ITT) was performed at the 6th week of experiment. At the end of the training period, the rats in all groups were sacrificed and blood was collected for the quantification of hematocrit and serum glucose, insulin, triglycerides, albumin, GH and IGF-1. Skeletal Muscle and hepatic glycogen levels and hepatic triglycericle, protein, DNA and IGF-I concentrations were also determined. Diabetes reduced the serum insulin, GH and IGF-I concentrations, and the hepatic protein/DNA ratio and IGF-1 concentrations, but increased serum glucose and triglycericle levels. Serum glucose removal during ITT was increased in the trained diabetic animals compared to sedentary control. Physical training reduced the serum glucose and triglycericle levels but increased the muscle glycogen content and restored the hepatic protein/DNA ratio and serum and hepatic IGF-I in diabetic rats. In conclusion, long-term chronic exercise improved the metabolic state and attenuated the reduction in serum and hepatic IGF-I concentrations caused by diabetes. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Diabetes mellitus; Insulin-like growth factor (IGF-1); Liver; Training